2021
DOI: 10.3390/w13233402
|View full text |Cite
|
Sign up to set email alerts
|

Legacy and Emerging Pollutants in an Urban River Stretch and Effects on the Bacterioplankton Community

Abstract: River contamination is due to a chemical mixture of point and diffuse pollution, which can compromise water quality. Polycyclic Aromatic Hydrocarbons (PAHs) and emerging compounds such as pharmaceuticals and antibiotics are frequently found in rivers flowing through big cities. This work evaluated the presence of fifteen priority PAHs, eight pharmaceuticals including the antibiotics ciprofloxacin (CIP) and sulfamethoxazole (SMX), together with their main antibiotic resistant genes (ARGs) and the structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Comparing the ndings from the long-term research by Nagy, et al [29] over the years, it can be noticed that concentrations of PAHs in water and sediment decreased dramatically. Moving to the second part of the PAHs level examination in the Danube River which was in the capital city, Visca, et al [31] evaluated the contamination in terms of PAHs level in the Danube River (only water samples) passing through Budapest with three locations inside the city. The samplings were performed in April 2017, November 2017, and October 2018.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the ndings from the long-term research by Nagy, et al [29] over the years, it can be noticed that concentrations of PAHs in water and sediment decreased dramatically. Moving to the second part of the PAHs level examination in the Danube River which was in the capital city, Visca, et al [31] evaluated the contamination in terms of PAHs level in the Danube River (only water samples) passing through Budapest with three locations inside the city. The samplings were performed in April 2017, November 2017, and October 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The samplings were performed in April 2017, November 2017, and October 2018. It should be mentioned; however, that information about the PAHs range is missing [31]. Caracciolo, et al [32] also conducted a study to monitor the PAHs level in Budapest at three different points without, however, revealing the coordinates of those sampling points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphate is a typical water contaminant that can be found in industrial discharge, residential wastewater, and agricultural runoff. The process of eutrophication, in which an excess of nutrients leads to an excessive growth of algae and other aquatic plants, can be triggered by excessive phosphate levels in water. This process lowers the water’s quality by reducing its oxygen content and harming aquatic life, , decreasing its quality. …”
Section: Introductionmentioning
confidence: 99%
“…The overall conclusion regarding the studies conducted for measuring the PAHs level in the Danube River within the framework frame of Hungarian borders is that most of these investigations were conducted in the upper part of the river, and with the latest sampling campaign in the period of 2014-2015 (Nagy et al, 2018). Other studies have reported PAHs level in the area of Budapest, however, with unclear conclusions due to missing information such as the PAHs ranges, sampling locations, and overlooking the sediments part, which is considered an important PAHs sink (Visca et al, 2021;Caracciolo et al, 2019). With a view to narrowing the gap in knowledge regarding PAHs concentration in the Danube River, the present investigation was designed to adequately investigate the spatial and temporal PAHs contamination of the river basin in Hungary.…”
Section: Introductionmentioning
confidence: 99%